Novel Approach for Encryption using Catalan Numbers - Devi Kakarla, V. Uma Karuna; Suneetha, CH. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In today’s fast-changing digital world, passwords or PIN numbers are needed for everything from financial transactions to confidential correspondence. This practice protects monitory exchanges, financial processes, and secret communications. Sharing a complex PIN or one-time password has emerged to strengthen this security paradigm and protect critical interactions. The Crypto Council for Innovation (CCI) has developed a complete PIN security architecture to improve security. This method relies on encrypted symmetric keys integrated into complex key block architectures. These structures include cautious key usage limits, strengthening the security system. These key blocks avoid the presumption that previously established keys can be reused, promoting dynamic key management and increased security. At the vanguard of these security advances, this research paper painstakingly explains password and PIN encryption and migration. This unique and stable secure communications system uses Catalan number sequences’ mathematical elegance. This novel method presents the recipient of encrypted communication with a lengthy, seemingly random sentence that contains the encrypted password or PIN. This encrypted payload is discretely dispersed throughout the text, making its identification and extraction difficult for malevolent actors. Importantly, both the sender and the recipient are blissfully unaware of the PIN characters’ precise positions, adding ambiguity that prevents illegal access. In conclusion, the digital landscape requires strong security to protect financial, secret, and covert transactions. Encrypted symmetric keys in dynamic key block structures, certified by the Crypto Council for Innovation, demonstrate a strong commitment to security. The encryption and migration method, which uses Catalan number sequences to hide passwords and PINs, shows the relentless search of impenetrable security in an increasingly linked world.